Research on diversity receive technology on wireless optical communication using subcarrier modulation - Dan CHEN; Xi-zheng KE (Tongxin xuebao)
Based on the log-normal model under the turbulence channel,the BPSK subcarrier modulated FSO system with spatial diversity was established.Under different scintillation distribution and different detectors,the error performance and diversity gain among three linear combining technologies were compared.The simulation results show that the performance improved of system by MRC is the best,followed by EGC,and SelC is poor.Spatial diversity is efficient to improve the performance and have strong ability on resistance to atmospheric channel decline.But on short link FSO system experiencing weak irradiance fluctuation,SelC spatial diversity would not be recommended.